Hallo Kons: Web-Based Guidance and Counseling Services to Improve University Students’ Well-being - Christiana, Ratih; Wardani, Silvia Yula; Suharni, Suharni; Mahmudi, Ibnu; Aji, Afara Dinan Sa'id Restu; Rahmawati, Shinta; Dwi, Puspita; Rivera, Alice Tonido (Buletin Konseling Inovatif, 2025)
This study aims to develop 'Hallo Kons' which is an innovation of website-based guidance and counseling services to improve the well-being of students at Universitas PGRI Madiun (UNIPMA), which include four areas of guidance and counseling services, namely: personal, social, learning and career. The method in this study is research and development (R&D). The subjects of the study were website experts, UNIPMA counselors and students of UNIPMA. The data analysis used was qualitative and quantitative, with data collection techniques using assessment sheets filled out by 4 experts: consisting of 2 website experts and 2 experts in the field of guidance and counseling, which showed the results of expert validation tests with an average value of 62.5 (good category), guidance and counseling experts with an average value of 61.5 (good category), then for the practical test carried out by 2 counselors with assessment indicators: (1) understanding, (2) Implementation, (3) Ease, then for small group trials on student user of Hallo Kons, a sig. value was obtained. (2-tailed) of 0.000 and it can be concluded that Hallo Kons is effective in improving the psychological well-being of students at Universitas PGRI Madiun (UNIPMA).